The Stage of Fulfilling the Real Convergence: The Case of Romania - Ioana M. MINDRICAN; Elena F. MATEI; Miruna M. VASILCA (Communications of International Proceedings, 2021)
This article analyzes and highlights aspects related to real convergence, as well as the sources of economic growth in Romania in the European context. The real convergence criteria aim at reducing the gaps between states in terms of the level of development and living conditions of the population. The Maastricht Treaty does not specify explicit criteria for real convergence, as is the case with nominal convergence, but nevertheless they play a key role in the economic stability of the state, especially Romania, taking into account the desire to join the Euro Area. The main real convergence criteria presented in this paper are the level of GDP / inhabitants, the degree of openness of the national economy in relation to the European economy, the structure of branches of the national economy, an indicator that can be measured as a percentage of GDP, labor costs and the migration level. Given that Romania has been a Member State of the European Union since 2007, its economic policy is realistic, as it is based on the harmonization of market forces with economic policy, based on the principle of cohesion, which supports the economic context through economic leverage, less developed regions. Compared to the way of presenting the information from the selected bibliography, in this paper are found only the essential aspects, the particularities of the chosen research topic, which finally provides an overview.
Keywords: Euro Area; real convergence; GDP; migration.